2015
DOI: 10.2519/jospt.2015.5460
|View full text |Cite
|
Sign up to set email alerts
|

Low Back and Lower-Limb Muscle Performance in Male and Female Recreational Runners With Chronic Low Back Pain

Abstract: Runners with chronic LBP exhibited diminished knee extensor strength compared to healthy runners. Male runners with chronic LBP demonstrated additional deficits in lumbar multifidus activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 39 publications
0
30
1
Order By: Relevance
“…Despite the premise that the erector spinae of subjects with low back pain are more susceptible to fatigue compared to healthy subjects 13,14 , some authors 15,21,22 that used similar methodology applied in our study also found no differences between groups with and without low back pain for the MF analysis.…”
Section: Muscle Fatigue Of the Spine Erectorcontrasting
confidence: 61%
“…Despite the premise that the erector spinae of subjects with low back pain are more susceptible to fatigue compared to healthy subjects 13,14 , some authors 15,21,22 that used similar methodology applied in our study also found no differences between groups with and without low back pain for the MF analysis.…”
Section: Muscle Fatigue Of the Spine Erectorcontrasting
confidence: 61%
“…Weakened quadriceps muscle strength can be lead to LBI [11]. Normally during run up phase, the generated GRF was absorbed by the knee joint and the lumbar spine and the reduction of quadriceps muscle strength resulted reduction of shock absorption on the knee joint and increased the force on the lumbar spine [18]. In contrast, a study interpreted that quadriceps muscle strength of non-dominant side was associated with LBP of young fast bowlers [11].…”
Section: Discussionmentioning
confidence: 99%
“…After surgery, treatment focused on education and loading the tissues over many weeks through a graded programme of loaded functional exercises and running retraining. In running retraining there is a strong need to pay attention to the specific capacity of the structure during the progression of sessions; the cumulative load of the structure for the current session; the reduction of the specific capacity of the structure during a session in progress; and not exceeding the specific capacity of the structure and running at the regular pace 21 54–56 65–68 76 77. Indeed running speeds below 12 km/hour seem to be ideal and reduce the risk of injury to the joint 76 77…”
Section: Discussionmentioning
confidence: 99%
“…The primary goal of these strategies was to optimise the dosage of loading stress to reduce the risk of RRIs even if it does not always lead to an improvement in the running biomechanics immediately on implementation (figure 4; video 1). 21 54–56 65–68 The physical therapy programme was balanced with other interventions to include the management of psychosocial aspects of the pain experience, negative illness perceptions, education, maladaptive cognitions and coping strategy 50–53 60…”
Section: Outcome and Follow-upmentioning
confidence: 99%